Citação por meio eletrônico - Oya, Norberto (2023)
This dissertation presents a study of summons mainly serviced electronically. This is a resource that stemmed from Law n. 14,195/2021, which redrafted article 246 of CPC (Brazilian Civil Code)/2015 and would be preferred to other means served by mail or publication, by court officials or by clerks of the court in case the defendant attends their office. The same legal rule commissioned the regulation to the National Council of Justice. This innovative legislative stance is a result of the conversion of Provisional Presidential Decree n. 1,040/2021, and it is subject to the analysis of the Federal Supreme Court, through direct action for the declaration of unconstitutionality n. 7005/STF. The electronic summons has its origin in Law n. 11,419/2006, which regulates the computerization of the judicial process. Article 20 inserted item IV to article 221 of CPC/1973 and introduced the option for electronic summons, which would be regulated by its own law. The original wording of article 246, item V of CPC/2015, reproduced the content of item IV of article 221 of CPC/1973, but omitted the adjective “own”, which designated the feminine noun “law”. Notwithstanding, this work begins with an approach to the procedural principles that surround the summons and then, contemplates the entire history of this doctrine showing its relevance in the civil procedural legal system. It is evidenced that the summons dates back to the period of creation of the universe, described in the Bible, but it is shaped in Roman law and remains present in the several later legislations. Despite some open points that can be improved, the summons is a contemporary doctrine within the electronic process